Denial of the Rohingya Genocide: Problematising Daw Aung San Suu Kyi and the Rule of Law in Postcolonial Myanmar - Wendell Gleen P Cagape (Otoritas : Jurnal Ilmu Pemerintahan, 2020)
As the world condemns the genocide, Myanmar and Daw Aung San Suu Kyi’s government denied it and refused to accept it and argued that it sanctioned under the rule of law. This paper problematises these questions:, What is the rule of law in Myanmar? And why do they deny it? This study is qualitative in which pages of transcripts of speeches perused to find themes, settings, and meanings attributed to problematising Daw Aung San Suu Kyi and the rule of law in post-colonial Myanmar. These speeches delivered in public from 2016-2018. In analysing her speeches, the paper uses Foucauldian Discourse Analysis. On the part of Daw Aung San Suu Kyi, it found that problematising her actions and silence over the Rohingya genocide influenced her late father’s role. She continued to claim that her military father is the father of the Burmese military. She had special relations in incarceration with the army generals during her house arrest. She focused on the democratic transition which she promised in the 2015 election.  This study reveals that this rule of law has purely political narratives because the generals are not accountable. This paper subsumes ongoing legal reforms in Myanmar.